Lexical combinatorics and meaning profiling of the lexeme embryo in the discourse of bioethics - Cozma, Ana-maria; Lehtonen, Kim (MODERN LANGUAGE SOC, 2025)
This article studies the lexical combinatorics of the word embryo and the way in which the meaning of this word is profiled from one phrase to another. The study was conducted using a bioethics corpus composed of institutional speeches, on the one hand, and comments from Internet users, on the other hand. From this corpus, we extracted using a concordancer all the phrases in which the word embryo occurs, regardless of their frequency. The phrases thus listed are presented first from the point of view of syntactic combinatorics, then from the point of view of lexical combinatorics, and constitute the data that we will analyze. Thus, although extracted from actual speeches, the phrases have undergone simplifications that make them more at a prediscursive level. To conduct the study on these syntagms, the chosen analysis model is that of the Semantics of Argumentative Possibles (SPA) of Olga Galatanu (2018, 2022), on which we grafted the notion of profiling (Cadiot & Visetti 2001), understood as the result of a process of convocation-evocation, according to the vision of Gestalt compositionality of Victorri et al. (Victorri & Fuchs 1996; Victorri 1997). The analysis itself consists of identifying the argumentative associations activated by the syntagms: the argumentative deployments, on the one hand, and the associations evoked due to the lexical combinatorics, on the other hand.